Sliding mode control of an innovative single-switch three-level active rectifier - Monteiro, Vítor Duarte Fernandes (2019)
This paper presents the sliding mode control (SMC) applied to an innovative active rectifier. This proposed active rectifier is constituted by a single-switch, and operates with three voltage levels, evidencing a set of advantages when compared with conventional approaches of power factor correction topologies. Taking into account the diversity of applications for this type of power converter, the SMC is used in order to obtain a robust current tracking. Since the active rectifier is controlled according to the ac grid-side current, the error between such current and its reference is determined, and by employing the SMC, this error is minimized during each sampling period with the objective of selecting the state of the single-switch. A comprehensive description about the SMC implementation, supported by the overall operation of the active rectifier, is presented throughout the paper. The obtained computational results for a set of different operating conditions, comprising significant power ranges and sudden variations, confirm the accurate application of the SMC when applied to the proposed single-switch three-level active rectifier. A comparison is also established with other current control, allowing to confirm the precise application of the SMC strategy.